Central node dissection in papillary thyroid carcinoma in the era of near-infrared fluorescence - Kuczma, Paulina; Demarchi, Marco Stefano; Leboulleux, Sophie; Trésallet, Christophe; Mavromati, Maria; Djafarrian, Reza; Mabilia, Andrea; Triponez, Frédéric (Frontiers in Endocrinology, 2023)
The most common site of lymph node metastases in papillary thyroid carcinoma is the central compartment of the neck (level VI). In many patients, nodal metastases in this area are not clinically apparent, neither on preoperative imaging nor during surgery. Prophylactic surgical clearance of the level VI in the absence of clinically suspicious lymph nodes (cN0) is still under debate. It has been suggested to reduce local recurrence and improve disease-specific survival. Moreover, it helps to accurately diagnose the lymph node involvement and provides important staging information useful for tailoring of the radioactive iodine regimen and estimating the risk of recurrence. Yet, many studies have shown no benefit to the long-term outcome. Arguments against the prophylactic central lymph node dissection (CLND) cite minimal oncologic benefit and concomitant higher operative morbidity, with hypoparathyroidism being the most common complication. Recently, near-infrared fluorescence imaging has emerged as a novel tool to identify and preserve parathyroid glands during thyroid surgery. We provide an overview of the current scientific landscape of fluorescence imaging in thyroid surgery, of the controversies around the prophylactic CLND, and of fluorescence imaging applications in CLND. To date, only three studies evaluated fluorescence imaging in patients undergoing thyroidectomy and prophylactic or therapeutic CLND for thyroid cancer. The results suggest that fluorescence imaging has the potential to minimise the risk of hypoparathyroidism associated with CLND, while allowing to exploit all its potential benefits. With further development, fluorescence imaging techniques might shift the paradigm to recommend more frequently prophylactic CLND.